Enhancing thermal runaway characterization in NMC811 lithium-ion batteries through laser-induced triggering - García, Antonio; Monsalve-Serrano, Javier; de Vargas Lewiski, Felipe; Guaraco-Figueira, Carlos (Journal of power sources, 2024)
To further explore the thermal runaway phenomenon of lithium-ion batteries, this study examines the thermal runaway characteristics of 18,650 cylindrical cells with 811 nickel-manganese-cobalt cathode chemistry under laser irradiation. This abuse method allows precise energy quantification and localized heating compared to more conventional abuse methodologies. The study subjects NMC811 cells of different charge states to laser irradiation across a spectrum of power levels, elucidating three distinct durations of abuse and recording the phenomena by the Schlieren imaging technique. The results show that at least 346.5 J of laser irradiation is required to induce thermal runaway in the sample batteries, presenting different delays depending on the State of Charge. The optical technique applied in this study allows for the characterization of the venting process and the thermal runaway behavior, finding different venting stages that show an evolution from slow and laminar flow to a turbulent flow until the venting of particle matters, leading to an unstoppable chain reaction. These findings significantly contribute to understanding the intricate dynamics preceding the thermal runaway phenomenon, offering a pivotal advancement in lithium-ion battery safety comprehension. •Laser irradiation allows evaluating thermal runaway from controlled local heating.•Laser Irradiation tests characterize the energy required to induce thermal runaway.•Cells with lower state of charge require more laser energy to reach thermal runaway.•Thermal runaway vented gases are ignited by the presence of hot particles.